2021
DOI: 10.1186/s12904-021-00843-x
|View full text |Cite
|
Sign up to set email alerts
|

“The system is well intentioned, but complicated and fallible” interviews with caregivers and decision makers about palliative care in Canada

Abstract: Background Canadian palliative care (PC) philosophy seeks to support individuals in a person-centered and sensitive manner. Unfortunately, philosophy does not necessarily translate into practice and this divide may leave patients without appropriate care at the end of life, causing distress for some families. The primary goal of the study was to identify key factors affecting perceptions of quality PC from the perspective of informal caregivers and decision makers (e.g., program managers) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Over 90% of respondents (both users and non-users) relied on the community (family/friends/neighbors/community organizations) to support them before and after bereavement and reported that this informal support was helpful in attending to practical, social, emotional, and spiritual support needs. Other studies support this finding [19][20][21]. The primacy of support from social networks is at the heart of public health approaches to palliative and end of life care which have the potential to enhance integration of services and provide a comprehensive approach that engages the assets of local communities [1,22].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Over 90% of respondents (both users and non-users) relied on the community (family/friends/neighbors/community organizations) to support them before and after bereavement and reported that this informal support was helpful in attending to practical, social, emotional, and spiritual support needs. Other studies support this finding [19][20][21]. The primacy of support from social networks is at the heart of public health approaches to palliative and end of life care which have the potential to enhance integration of services and provide a comprehensive approach that engages the assets of local communities [1,22].…”
Section: Discussionmentioning
confidence: 85%
“…In the absence of formal case managers, family carers must be supported to develop their capacity in this role if care is to be as effective as possible. Family carer support needs to be at two levels: to help family carers care for the ill person but also to help care for themselves [ 18 , 19 , 20 ]. This can be achieved by instigating a system that assesses and addresses carer support needs, collects regular consumer feedback, and co-designs service improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, some care caregivers felt that during a crisis, they had to rely on ambulances and the use of the emergency department (ED). Caregivers cited emotional and psychological needs as well as loneliness among those receiving PC [ 45 ]. This rich qualitative data was used to guide QI development in the next phase of the project.…”
Section: Methodsmentioning
confidence: 99%
“…Challenges experienced by palliative family caregivers have been well documented for decades. These include taking on primary responsibility for care without that role necessarily being respected by healthcare providers, challenges navigating a complex system, and physical and emotional effects from heavy caregiving responsibilities [34][35][36][37]. These challenges were exacerbated by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%